Use of Modeling and Positive Reinforcement Techniques to Regulate Indiscriminate Physical Proximity in a 5 year-Old Girl in Foster Care: Case Study - Morera Vargas, Ileana (2020)
The objective of this article is to describe a unique case study involving a 5 year-old girl, who was the victim of physical abuse, neglect and sexual abuse, in a foster care program. According to DSM-5 criteria, she presented with signs of Disinhibited Social Relation Disorder, an absence of reticence to approach and interact with adults, both known and unknown to her, in different surroundings, affecting her interpersonal relationships and constituting a risk factor for new instances of sexual abuse. We worked with modeling modalities and positive reinforcement, focused on Cognitive Behavioral Game Therapy, as well as a focus on environmental therapy, with the goal of modifying inappropriate patterns of affection and close physical contact and approach. We attempted to satisfy her need for physical and emotional contact through limited and positive proximity, which could then constitute a protective tool for her, and could facilitate the building of assertive interpersonal relationships.